2019
DOI: 10.1016/s2215-0366(19)30214-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk of suicide and repeat self-harm after hospital attendance for non-fatal self-harm in Sri Lanka: a cohort study

Abstract: Summary Background Evidence from high income countries (HICs) suggests that individuals who present to hospital after self-harm are an important target for suicide prevention, but evidence from low and middle-income countries (LMICs) is lacking. We aimed to investigate the risk of repeat self-harm and suicide, and factors associated with these outcomes, in a large cohort of patients presenting to hospital with self-harm in rural Sri Lanka. Methods In this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 22 publications
3
48
3
1
Order By: Relevance
“…This study identified that being male was associated with an increased risk of repetition and method-switching. There is little consensus in the literature in terms of gender-based differences in repetition risk, with our findings akin to some [ 15 , 39 , 40 ] and different from existing research [ 12 , 41 , 42 ]. Similarly, in relation to method-switching, males have been identified as at increased risk by this study and similar research [ 24 ].…”
Section: Discussioncontrasting
confidence: 99%
“…This study identified that being male was associated with an increased risk of repetition and method-switching. There is little consensus in the literature in terms of gender-based differences in repetition risk, with our findings akin to some [ 15 , 39 , 40 ] and different from existing research [ 12 , 41 , 42 ]. Similarly, in relation to method-switching, males have been identified as at increased risk by this study and similar research [ 24 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The incidence of nonfatal self-poisoning actually increased [107], but the use of less lethal pesticides caused the national total suicide rate to decline [65]. Additionally, most people who survive a first attempt do not repeat their act [8,11]. A similar effect could potentially be seen in India, especially with the broader bans that are taking place in 2018 and 2020.…”
Section: Discussionmentioning
confidence: 99%
“…They are often used impulsively for suicide attempts in times of acute stress [7], frequently with less than 30 min of planning [5]. Surviving an act of pesticide self-poisoning allows people to receive support from their family, community, and medical and psychosocial services, and most suicide attempts are not repeated [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…This nding may also partially explain the lower repetition rates of self-harm, observed in Sri Lanka. [6,27] In this Sri Lankan context a greater focus on non-psychiatric and medical interventions many be appropriate. In rural Sri Lanka, self poisoning seems to be the preferred method of dealing with di cult situations [28].…”
Section: Rates Of Psychiatric Morbiditymentioning
confidence: 99%